Reflections on the changing landscape of apologetics. (21st July 2021) - Pickering, David
Abstract: This essay investigates one aspect of the relationship between contemporary apologetics and cultural studies. It begins with a consideration of Avery Dulles' famous History of Apologetics . While noting the many virtues of Dulles' work, it critiques his lack of attention to the role of imagination, emotion, narrative, and personal testimony. The essay argues that Dulles' work shows how constricted the study of apologetics has often been in comparison with its practice. The essay goes on to note recent developments in research into apologetics which have begun to apply recent philosophical and theological interest in narrative, imagination, and the emotions to this field. It explores the increasingly sophisticated conceptual apparatus available for this task, in particular the concepts of the Social Imaginary and the Overton Window. Finally, the essay attempts a dialogue with certain aspects of secular advocacy, in relation to the role of emotion in the public square. It concludes that the use of conceptual resources from other disciplines, and engagement in dialogue with secular advocacy, may be of benefit to apologetics.